Credibility Beyond Replicability: Improving the Four Validities in Psychological Science. (April 2022) - Vazire, Simine; Schiavone, Sarah R.; Bottesini, Julia G.
Psychological science's "credibility revolution" has produced an explosion of metascientific work on improving research practices. Although much attention has been paid to replicability (reducing false positives), improving credibility depends on addressing a wide range of problems afflicting psychological science, beyond simply making psychology research more replicable. Here we focus on the "four validities" and highlight recent developments—many of which have been led by early-career researchers—aimed at improving these four validities in psychology research. We propose that the credibility revolution in psychology, which has its roots in replicability, can be harnessed to improve psychology's validity more broadly.